Eksplorasi Pemodelan Informasi Bangunan atau Building Information Modelling (BIM) Dalam Penyelenggaraan Bangunan - Ahmad Latiffi, Aryani; Sulum, Muhd Nur Suhairul; Bilal, Kamalludin (Research in Management of Technology and Business, 2020)
Building maintenance management methods using Building Information Modelling (BIM) technology can improve the quality of the maintenance. However, the use of BIM is still lacking in practice for building maintenance. The objectives of this study is to examine the challenges to implement BIM for improving the quality of building maintenance and to identify ways that can be practiced to improve the quality of building maintenance by using BIM. To achieve the objectives, face-to-face interviews were conducted with building maintenance contractors that are using BIM and have experienced using BIM for building maintenance in the states of Johor and Selangor. The results of the interviews found that the challenges in implementing BIM for building maintenance such as the high cost of software and lack of skilled manpower in handling the technology. In addition, the ways that can be practiced to improve the quality of building maintenance by using BIM such as improving knowledge on BIM by participating and attending relevant training as well as the preparation of relevant guidelines. This study benefits the construction industry in terms of building maintenance aspects where it can help contractors make planning and also speed up the maintenance process.